Viewing Sexual Violence : Audience Responses to Game of Thrones - Korhonen, Venla; Koistinen, Aino-Kaisa; Korpua, Jyrki; Välisalo, Tanja (University of Nottingham, 2024)
In this article, we examine audience responses to representations of sexual violence in the fantasy television series Game of Thrones (GoT, 2011–2019) by analysing online survey data gathered by the international Game of Thrones Research Project (2016‒2017). GoT has been subject to heated debate over its violent content, particularly the representations of rape. Many scholars have analysed the series’ representations of violence, but relatively few studies focus on the show’s audiences, let alone on the reception of sexual violence. This article seeks to fill this gap in earlier research by analysing the complex ways that viewers experience sexual violence in GoT. Our study sheds light on the ways in which audiences negotiate their (gendered) viewing experiences in the context of their personal histories and in relation to the functions and conventions of media representations, narratives, and cultural discourses.
Keywords: väkivalta; televisio-ohjelmat; naiset; fanius; yleisötutkimus; raiskaus; populaarikulttuuri; seksuaalirikokset; reseptio